Why Chavez in Venezuela? - Vivas, Leonardo (Tufts Archival Research Center, 2005)
Volume 25, Issue 1. Winter Vivas examines the rise to power of populist Venezuelan president Hugo Chavez, and warns that his political style may be a harbinger of things to come in the Andean region.